BERITA KRIMINALITAS DI KORAN BINTANG BORNEO EDISI BULAN JANUARI HINGGA JULI TAHUN 1930 - Haini, Nur (Langgong: Jurnal Ilmu Sosial dan Humaniora, 2023)
Research on crime news in the Bintang Borneo newspaper, which was reviewed from January to July 1930, had the aim of finding out the content of the news regarding these criminal acts. The background of the news is statements of a general and actual nature, broadcast by newspapers made by journalists for the benefit of readers (Irawan & Meinanda, 1981:10). This research uses a descriptive qualitative method and uses a historical analysis approach. Historical analysis is an analysis that relies on the aim of describing or reconstructing past events systematically and objectively, by collecting, evaluating, verifyingand connecting evidence to reveal facts and obtain strong conclusions. This research has certain characteristics, namely that thedata collected is not only primary (primary sources obtained from interviews and the researcher's own observations), but also secondary (secondary sources obtained from observations of other people). Apart from that, the data source obtained is in the form of additional data such as documents and related books. To determine the weight of the data, two types of criticism are carried out, namely (1) external: examining the authenticity of the data, and (2) internal: examining the accuracy or data correctness.